A phase-dependent photoluminescent discotic liquid crystal bearing a graphdiyne substructure. Issue 7 (4th January 2021) - Yu, Zhen; Chen, Xu-Man; Liu, Zhi-Yang; Wang, Meng; Huang, Shuai; Yang, Hong
Abstract : In this manuscript, a graphdiyne-derived discotic liquid crystal material exhibiting a tunable phase-dependent photoluminescence property is reported. Abstract : In recent years, graphdiyne and its derivatives with fascinating electro-optic properties have attracted tremendous scientific attention. Here we design and synthesize a graphdiyne-derived discotic liquid crystal material by decorating six wedge-shaped 3, 4, 5-tris(dodecyloxy)benzoate groups on the fundamental structural unit of graphdiyne, the dehydrotribenzo[18]annulene core. This graphdiyne-derived liquid crystal material exhibits a cubic phase and a hexagonal columnar phase at varied temperatures. Most interestingly, this molecule displays a tunable phase-dependent photoluminescence behavior. Under the irradiation of 365 nm wavelength ultraviolet light, the luminescent material emits pale blue, green and azure light in the cubic, hexagonal columnar and isotropic phases respectively. This graphdiyne-derived discotic liquid crystal with excellent optical characteristics might have application potentials in organic optoelectronic functional materials and devices.